Multiple autoimmune side effects of immune checkpoint inhibitors in a patient with metastatic melanoma receiving pembrolizumab. (January 2021) - Kethireddy, Nikhila; Thomas, Steffi; Bindal, Poorva; Shukla, Prateek; Hegde, Upendra
Introduction: Immune agents including anti-programmed death receptor-1 and anti-cytotoxic T-lymphocyte antigen-4 have been associated with numerous immune-related complications. Pembrolizumab, a programmed death-1 inhibitor, has been associated with a number of immune-related adverse events such as pneumonitis, colitis, hepatitis, hypophysitis, hyperthyroidism, hypothyroidism, nephritis, and type 1 diabetes. Case report: We present a rare case of an elderly male on pembrolizumab who suffered from four autoimmune toxicities including type 1 diabetes, pneumonitis, hypothyroidism, and polymyalgia rheumatica likely catalyzed by age-related immune activation. Management and outcome: Immunotherapy was indefinitely stopped, and patient was started on steroids for the immune-related adverse events with complete resolution of polymyalgia rheumatica. Thyroid dysfunction resolved once he started thyroid replacement therapy. His diabetes is well controlled with insulin and is followed by endocrinology. He continues on prednisone for immune-mediated pneumonitis with a good response with regular monitoring via computed tomography scans and pulmonary consultation. Discussion: Few cases wherein multiple toxicities are seen within one patient are reported. Aging appears to be a risk factor for immune-related adverse events. Aging is associated with an increased incidence of autoimmunity as programmed death-1 ligand expression represents an important mechanism that tissues use to protect from self-reactive effector T cells. Programmed death-1 blockade breaks this protective mechanism and enhances autoimmune diseases. Therefore, close monitoring and extreme vigilance is warranted while using immune checkpoint inhibitors including pembrolizumab as multiple toxicities can occur within a short span of infusion, especially in elderly individuals. Prompt discontinuation and the use of a multidisciplinary team are prudent to prevent further morbidity and mortality.